GERAKAN MASYARAKAT HIDUP SEHAT DALAM MENCEGAH TERJADINYA PENYAKIT GIGI DAN MULUT - I Wayan Suanda (Jurnal Kesehatan Gigi (Dental Health Journal), 2018)
Health development is essentially an effort carried out by all components of the Indonesian Nation which aims to increase the awareness, ability and ability of healthy life for everyone. At present, Indonesia is experiencing a change in disease patterns which are often called epidemiological transitions which are characterized by increased mortality and illness due to non-communicable diseases (PTM) such as stroke, heart disease, diabetes and others.Oral health is a fundamental part of health in general and is able to improve the quality of life. Oral health which was originally called dental health is the well-being of the oral cavity, including the teeth, and its supporting tissue, which can function optimally and free from painBasic Health Research in 2013, showed that the population with problems with teeth and mouth in the Province of Bali reached 24%, Behavior in the selection of dental health also showed that people suffering from dental and oral diseases in the Province of Bali only 38.8% sought treatment / care from dental medical personnel. Most (91.8%) of the population aged 10 years and over in Bali Province brush their teeth every day, but only 4.1% behave correctly in brushing their teeth.Possible steps that can be taken to reduce dental morbidity are through counseling on dental and oral health and habituation to carry out Germas in each activity. The real forms that can be done include: 1 Develop dental health education materials that emphasize the importance of the pattern of Germas activities in preventing dental and oral diseases,  2.  Familiarize the community early on to consume fruits and vegetables, check their teeth regularly, minimize smoking and consume alcohol.This implementation will be better done early, for example starting in pre-school children.